Steinert's disease. A case report - Liubka María Pérez Mederos; Cecilio González Benavides; Francisco Rodríguez Denis (Acta Médica del Centro, 2008)
Myotonic dystrophy (DM) or Steinert's disease is the most common muscular dystrophy in adults, and is the second most common muscular dystrophy after Duchenne muscular dystrophy. It is an autonomus dominant genetic disorder affecting one of each 8000 individuals. Onset is usually in the second or third decade and the life span of affected individuals is typically six decades. It is characterized by weakness and muscular atrophy of the voluntary muscles of the eyes, face, neck, arms and legs, myotonia, posterior subcapsular iridescent cataracts, nervous conduction defects, endocrine changes, cognitive deficit and frontal bald. Muscles related to involuntary activities such as swallowing and breathing, as well as those surrounding the internal organs such as the upper and lower digestive tracts, the urinary bladder, and the uterus may also be affected as the disease progresses in an individual. The disease shows the genetic phenomenon of potentialization and anticipation. We show a patient´s case, that arrived to our clinic suffering from muscular atrophy for more than fifteen years. Because of clinical features the diagnosis of Steinert´s diseases was suspected. A review of the most common clinical features of this disease was done. The patient was examined by the neurologist, ophthalmologist, neurophysiologist, genetics and family doctors and it was found that the clinical and neurophysiological features indicated the presence of the Steiner´s disease. All studies made sure the diagnose of Steinert´s disease. It was found during the medical interview that his father and his older brother suffered from the same symptoms of the disease, which had begun around the forty years. Both of them died because of other causes.